Correlation Between Knowledge and Perception with The Willingness Of Human Papillomavirus Vaccination In Adolescents - Maulida, Mutia; Samaria, Dora; Ismail, Rita; Marcelina, Lina Ayu (Journal of Islamic Nursing, 2025)
The HPV vaccine has been proven effective in reducing cervical cancer. Currently, the free HPV vaccination program is accessible for 11-12-year-old girls, while those outside this age range must undergo self-funded vaccination at healthcare facilities. This quantitative cross-sectional study using Spearman Rank correlation aimed to determine the relationship between knowledge, perception, and willingness to receive HPV vaccine among 190 girl students from a junior high school in Jakarta. Stratified random sampling was employed. The results showed that the average age of respondents was 13.97 years, with the majority in grade 9, parents with high school/equivalent education, income below the minimum wage, and had never received information about HPV. Spearman test results a p-value = 0.000 and r = 0.389 for the variable of knowledge and willingness to vaccinate indicating there is significant relationship, and a p-value = 0.036, r = 0.153 for the variable of perception and willingness indicating there is relationship between the two. There is a relationship between knowledge and willingness to receive HPV vaccine, as well as between perception and willingness, with both showing a positive correlation. It is hoped that the HPV vaccination program will be optimized among adolescent girls to achieve WHO target.